2007
DOI: 10.1074/jbc.m608104200
|View full text |Cite
|
Sign up to set email alerts
|

The Werner Syndrome Helicase Is a Cofactor for HIV-1 Long Terminal Repeat Transactivation and Retroviral Replication

Abstract: (1) have demonstrated that WRN contributes to general RNA pol II 4 -dependent transcription, although its mechanism remains unclear. Interestingly, these authors found that a 27-amino acid direct-repeat sequence strongly activated transcription in yeast two-hybrid experiments, independent of WRN 3Ј 3 5Ј DNA helicase activity (1) (Fig. 1A) suggesting that WRN interacts with cellular factors to modulate RNA pol II-dependent transcription. The WRN protein localizes to nucleoli and the nucleoplasm of transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…For immortalized WRN Ϫ/Ϫ WS fibroblasts, Sharma et al (11) concluded that WRN participates in the recruitment of PCAF/P-TEFb-containing transcription complexes to HIV-1 LTR. Taken together with their findings, the RelA/p50 activation-mediated increase in association of WRN to the LTR is expected to result in enhanced recruitment of the PCAF/PTEFb-containing transcription complexes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For immortalized WRN Ϫ/Ϫ WS fibroblasts, Sharma et al (11) concluded that WRN participates in the recruitment of PCAF/P-TEFb-containing transcription complexes to HIV-1 LTR. Taken together with their findings, the RelA/p50 activation-mediated increase in association of WRN to the LTR is expected to result in enhanced recruitment of the PCAF/PTEFb-containing transcription complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence-WRN was previously reported to be tethered on the HIV-1 LTR in the presence of the viral transactivating Tat protein (11). However, the mechanisms underlying WRN recruitment to LTR are still unknown (11).…”
Section: Wrn Recruits Hiv-1 Promoter Via Nf-b Bindingmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Not surprisingly, drugs against cellular cofactors have high toxicity, but are still being pursued as options in the event of failure of HAART chemotherapy. Other recently identified cofactors in activation of HIV transcription include the Werner's syndrome helicase 5 and p90 ribosomal S6 kinase 2 (RSK2). 6 There has also been a great deal of interest regarding the TAR-binding protein (TRBP) and its effects on HIV replication.…”
Section: The Repertoire Of Potential Hiv Targets Is Expandingmentioning
confidence: 99%